The Contribution of Journalistic Knowledge to Students’ Skills in Writing News: A Study of Correlational Analysis - Wismanto, Agus; Asropah, Asropah; Arifin, Zaenal (Journal of Languages and Language Teaching, 2023)
Journalistic knowledge serves as a robust underpinning upon which learners can refine and enhance their writing abilities, specifically in the domain of news composition. The multifaceted landscape of journalism incorporates a medley of elements that collectively contribute to the cultivation of effective writing skills. The mastery of these facets plays a pivotal role in augmenting students' proficiency in articulating their ideas cogently, engaging their audience adeptly, and ensuring the meticulous conveyance of information. Against this backdrop, the present study endeavors to explore the substantive role played by journalistic knowledge in improving students' skills in writing news. To attain the research aim, the researchers applied a correlational study to find out the correlation between journalistic knowledge and students’ skills in writing news. The participants of the study consisted of 51 students of Indonesian language and literary education at the University of PGRI Semarang. The sample was taken using a simple random sampling technique. The data were collected using tests. Based on the data analysis, there is a correlation between journalistic knowledge and students’ skills in writing news. It means that the components of journalistic knowledge such as understanding the fundamental news values such as timeliness, prominence, proximity, conflict, and human interest, have contributed to helping students in writing news.